Assessing Supply Chain Quality Management Indicators: A Roadmap to Operational Excellence at Al-Zawraa General Company's Altahady Site - Saad Alwan, Ali; Ali Jasim, Nagham (Journal of Economics and Administrative Sciences, 2024)
This research endeavors to assess and enhance supply chain quality management at the Al-Tahady Site of Al-Zawraa General Company. The primary objective is to evaluate a comprehensive set of supply chain quality management indicators and provide a strategic roadmap for achieving operational excellence. The research problem addressed in this study revolves around the need to improve supply chain quality management practices. Despite the inherent challenges in real-world supply chain research, particularly in data acquisition and information gathering, this study is resolute in its mission. Beyond analysis, the researcher seeks to propose practical application mechanisms to drive tangible benefits for the company in attaining its operational goals. The examination of key supply chain quality management indicators reveals significant insights. Notably, the compliance rate consistently falls within the range of (1.04%) to (1.24%), affirming unwavering commitment to meeting purchase orders and contract standards. Transmission accuracy exhibits a parallel consistency, ranging between (1.04%) and (1.24%), signifying a remarkable precision in deliveries. The punctuality commitment is evidenced by on-time delivery rates, fluctuating from (91%) to (93%). Additionally, this study unveils fluctuations in supplier lead times, varying from (0.16%) to (0.55%). These variations serve as valuable signals, highlighting areas ripe for supplier management improvement. Furthermore, the prudent cost management practices implemented by the company are substantiated by total procurement costs ranging from (239,400,000) to (277,200,000). this research constitutes a concerted effort to elevate supply chain quality management at Al-Zawraa General Company's Al-Tahady Site. Its findings provide actionable insights aimed at enhancing supply chain performance, boosting customer satisfaction, and fortifying competitiveness.